Pengaruh Komitmen Organisasional, Kompensasi, dan Disiplin Kerja terhadap Kinerja Pegawai Yayasan Bina Insan Mulia Bekasi - Rosyidah Nurhidayati; Kusuma Candra Kirana; Ignatius Soni Kurniawan (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the effect of organizational commitment, compensation and work discipline on the performance of employees of Yayasan Bina Insan Mulia Bekasi. This research is a quantitative research and primary data is taken using a questionnaire taken by accidental sampling on 68 respondents. Data were collected through direct surveys and then processed using multiple linear regression analysis. The results showed that organizational commitment had a significant positive effect on employee performance. The results show that compensation and work discipline have no significant effect on employee performance. Keywords: work discipline, employee performance, organizational commitment, work compensation.